Production and characterization of acidophilic xylanase from wood degrading white rot fungus by solid-state fermentation of wheat straw - Tariku Abena; Addis Simachew (Heliyon, 2024)
Xylanases (EC 3.2.1.8) catalyze the breakdown of xylan, which is the second most abundant polysaccharide in plant cell walls. Biological catalysts have gained greater global attention than chemical catalysts in different industrial processes because they are highly selective, easy to control and have a negligible environmental impact. The aim of this study was to investigate the xylanolytic potential of white-rot fungi, optimize their physicochemical conditions and characterize the resulting xylanase. Sixty-eight white-rot fungus (WRF) isolates were screened for their xylanolytic potential and growth conditions for maximal xylanase production using cheap agricultural residue (wheat straw) as the sole carbon source. Five WRF isolates with high xylanase yields (73.63 ± 0.0283–63.6 ± 0.01247 U/ml) were selected by qualitative and quantitative screening methods. The optimum xylanase production occurred at pH 5.0 and 28 °C. Solid-state fermentation (SSF) yielded a high amount of xylanase. The highest xylanase activity (80.9–61.274 U/mL) was recorded in the pH range of 5.0–6.5 and at 50 °C. The metal ions Mg2+, Ca2+ and Mn2+ enhanced the activity of xylanase (127.28–110.06 %), while Cu2+, Fe2+ and K+ inhibited the activity with 43.4–17 % losses. The km and Vmax were 0.32–0.545 mg/mL and 86.95–113.63 μmol/min/mg, respectively. This finding indicates that wheat straw can be used for large-scale xylanase production under SSF conditions. The pH and temperature profiles and stabilities indicate that the xylanase produced in the present study can be applied in food and animal feed industries.